2005
DOI: 10.1007/s00467-005-1857-1
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-hour ambulatory blood pressure monitoring in infants and toddlers

Abstract: During the past several years, 24-hour (24-h) ambulatory blood pressure monitoring (ABPM) has become a useful tool for the diagnosis and management of children and adolescents with elevated blood pressure (BP). Some reports have also provided blood pressure nomograms for particular devices. However, there are very few reports of the use of this method in very young children. In our study we investigated the applicability of ABPM in 97 healthy infants and toddlers, aged from 2 to 30 months. A satisfactory ABPM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 29 publications
1
25
0
1
Order By: Relevance
“…ABPM is a valuable tool for use in children of all ages with suspected hypertension [2,16], but we have shown that interpretation of ABP records may be influenced by a degree of subjectivity leading to differing conclusions. This variability in reporting could be reduced by consensus regarding standardised interpretation; however, until further research provides more evidence, we suggest that the guidelines of Lurbe, Sorof and Daniels [11] be adopted.…”
Section: Discussionmentioning
confidence: 97%
“…ABPM is a valuable tool for use in children of all ages with suspected hypertension [2,16], but we have shown that interpretation of ABP records may be influenced by a degree of subjectivity leading to differing conclusions. This variability in reporting could be reduced by consensus regarding standardised interpretation; however, until further research provides more evidence, we suggest that the guidelines of Lurbe, Sorof and Daniels [11] be adopted.…”
Section: Discussionmentioning
confidence: 97%
“…112 Varda and Gregoric studied 97 infants and toddlers aged 2 to 30 months. 78 They noted no differences in ABPM values in relation to gender. There was also a smaller degree of nighttime dipping.…”
Section: Distribution Of Bp Values On the Basis Of Abpm Normative Datmentioning
confidence: 94%
“…One limitation noted was that the smallest available cuff was too large for some infants. 78 Gellermann et al obtained useable recordings in 77% of 101 children 3 to 6 years of age with and without renal disease and/or hypertension, with the ability to obtain useable recordings improving with age. 79 One half of the children diagnosed with high BP in the clinic setting were actually found to have normal ABPM, 80 emphasizing the use of ABPM in the diagnosis of hypertension.…”
Section: Ages Studied With Abpmmentioning
confidence: 99%
“…Even with these apparent limitations in equipment, ABP monitoring has been used successfully in many different centers, even in children as young as 2 years of age [8]. The ability to obtain complete recordings varies, however, depending on the population.…”
Section: Introductionmentioning
confidence: 99%